Asuhan Akupunktur Pada Penderita Xiao Ke di Rumah Sehat Ath-Thib Holistic Tangerang - Ika Cahyanti; Puspo Wardoyo; Ikhwan Abdullah; Amal Prihatono (Malahayati Nursing Journal, 2026)
ABSTRACT Xiao Ke is a term in Chinese Medicine that describes a disease condition similar to the characteristic symptoms of Diabetes Melitus in Western Medicine, including excessive thirst (polydipsia), excessive appetite (polyphagia), frequent urination (polyuria), weight loss, and body weakness. Acupuncture is considered a safe, rational, effective, affordable, and natural treatment option and serves as an alternative therapy to reduce the incidence of Xiao Ke or Diabetes Melitus. This case study aimed to determine the benefits of acupuncture care in a patient with Xiao Ke at Rumah Sehat Ath-Thib Holistic Tangerang. The study was conducted as a single case study over six therapy sessions on a 44-year-old male participant with Diabetes Melitus. Data collection techniques included observation (Wang), interview (Wen), listening and smelling (Wen), and palpation (Qie) in accordance with Traditional Chinese Medicine diagnostic standards. The selection of acupuncture points was based on the Yang Xiao Zheng syndrome, with the therapeutic principle of nourishing Yin and clearing heat pathogens (deficiency-type). The evaluation results showed that the treatment objectives were achieved and the problems were resolved, indicated by a decrease in blood glucose levels and improvement in the participant’s condition. Supporting factors that contributed to the success of the acupuncture care included good cooperation between the researcher and the participant in providing and undergoing therapy, as well as adherence to the given recommendations. Keywords: Diabetes Melitus, Xiao Ke, Acupuncture Therapy.  ABSTRAK Xiao Ke merupakan istilah dalam Chinese Medicine yang menggambarkan suatu kondisi penyakit mirip dengan gejala khas Diabetes Melitus (berupa rasa haus berlebihan (polidipsia), selera makan berlebihan (polifagia), sering buang air kecil (poliuria), penurunan berat badan, serta kelemahan tubuh) dalam Kedokteran Barat. Akupunktur menjadi salah satu pilihan pengobatan yang aman, rasional, efektif, murah, dan alami menjadi alternatif terpilih dalam menekan frekuensi penyakit Xiao Ke atau Diabetes Melitus. Penelitian studi kasus ini bertujuan untuk mengetahui manfaat Asuhan Akupunktur pada Penderita Xiao Ke di Rumah Sehat Ath-Thib Holistic Tangerang. Penelitian dilakukan dalam bentuk studi kasus tunggal selama enam sesi terapi pada satu orang partisipan laki-laki berusia 44 tahun yang memiliki penyakit Diabetes Melitus. Teknik pengumpulan data meliputi observasi (Wang), wawancara (Wen), pendengaran dan penciuman (Wen), dan perabaan (Qie) sesuai standar ilmu pengobatan Tiongkok. Pemilihan titik akupunktur didasarkan pada sindrom Yang Xiao Zheng dengan prinsip terapi yang diterapkan adalah memupuk Yin dan membersihkan patogen panas (bersifat xu). Hasil evaluasi terapi menunjukkan tujuan tercapai dan masalah teratasi yaitu penurunan kadar gula darah dan perbaikan kondisi partisipan. Faktor pendukung yang mempengaruhi keberhasilan dari asuhan akupunktur adalah adanya kerjasama yang baik antara penulis dan partisipan dalam memberi dan menjalani terapi serta saran yang diberikan. Kata Kunci: Diabetes Melitus, Xiao Ke, Terapi Akupunktur